Encapsulation of Graphene in the Hydrophobic Core of a Lipid Bilayer - Arjmandi-Tash, Hadi (Langmuir : the ACS journal of surfaces and colloids, 2020)
Theoretical simulations have predicted that a lipid bilayer forms a stable superstructure when a sheet of graphene is inserted in its hydrophobic core. We experimentally produced for the first time a lipid-graphene-lipid assembly by combining the Langmuir-Blodgett and the Langmuir-Schaefer methods. Graphene is sandwiched and remains flat within the hydrophobic core of the lipid bilayer. Using infrared spectroscopy, ellipsometry, and neutron reflectometry, we characterized the superstructure at every fabrication step. The hybrid superstructure is mechanically stable and graphene does not disturb the natural lipid bilayer structure